Clinically and Ultrasonographic Examination Findings in a Cow with Right Sided Abomasal Displacement and Traumatic Reticuloperitonitis - Baydar, Ersoy; Durmuş, Ali Said (Balıkesir Üniversitesi, 2022)
In this study, the results of clinical, ultrasonographic, and laparotomy examinations of a five-year-old dairy cow with right abomasal displacement and traumatic reticuloperitonitis are presented. A five-year-old Holstein cow who had recently given birth was brought to the veterinary teaching hospital with a history of depression, anorexia, constipation, arched backs, and bloat. A possible diagnosis of TRP and RDA was made based on the history and the findings of the clinical and ultrasonographic finding, and the cow was sent for surgery. An ultrasonographic examination revealed hyperechogenic fibrin deposits and anechogenic fluid pockets between the reticulum and the anterior dorsal blind sac of the rumen. It was discovered that the displaced abomasum is hypoechogenic, has fluid ingesta ventrally, and has a gas cap more dorsally. The reticulum's submerged and free foreign bodies were removed, and an abomasopexy procedure was performed. The day after the operation, the cow was able to eat and she gradually got better over the next few days. It was concluded that ultrasonography along with a clinical examination, is a useful adjunct tool for assessing the concurrent observed abomasal displacement and traumatic reticuloperitonitis.

Bu çalışmada, sağ abomazum deplasmanlı ve travmatik retiküloperitonitisli beş yaşlı süt sığırında klinik, ultrasonografik ve laparotomi muayene sonuçları sunulmaktadır. Yakın zamanda doğum yapmış beş yaşındaki Holstein inek, depresyon, iştahsızlık, kabızlık, sırtta kamburluk ve şişkinlik anamnezi ile veteriner eğitim hastanesine getirildi. Anamnez, klinik ve ultrasonografik muayene sonuçlarına dayanarak, TRP ve RDA'nın geçici teşhisi yapıldı ve inek ameliyata alındı. Klinik muayeneyi takiben, ultrasonografik incelemede, retikulum ile rumenin ön dorsal kör kesesi arasında hiperekojenik fibrin birikintileri ve anekojenik sıvı keseleri tespit edildi. Deplase olmuş abomazumun hipoekojenik olduğu, ventralde sıvı ve daha dorsalde gaz kesesine sahip olduğu belirlendi. Retikulumun batmış ve serbest yabancı cisimleri çıkarıldı ve abomazopeksi operasyonu yapıldı. Operasyondan sonraki gün ineğin iştahının açıldığı ve sonraki günlerde durumunun giderek normalleştiği bilgisi alındı. Ultrasonografinin klinik muayene ile birlikte eşzamanlı gözlenen sağ abomazum deplasmanı ve travmatik retiküloperitonitisi değerlendirmede yararlı bir yardımcı araç olduğu sonucuna varıldı.
Sağ Abomazum Deplasmanı ve Travmatik Retiküloperitonitisli Bir İnekte Klinik ve Ultrasonografik Muayene Bulguları
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi